Multi-parameter evaluation of the effect of processing conditions on meat protein modification. Issue 6 (June 2020) - Deb-Choudhury, Santanu; Haines, Stephen; Harland, Duane; Clerens, Stefan; van Koten, Chikako; Lee, Erin; Thomas, Ancy; Dyer, Jolon
Abstract: Evaluating the interconnecting effects of pH, temperature and time on food proteins is of relevance to food processing, and food functionality. Here we describe a matrix-based approach in which meat proteins were exposed to combinations of these parameters, selected to cover coordinates in a realistic processing space, and analyzed using redox proteomics. Regions within the matrix showing high levels of protein modification were evaluated for oxidative and other modifications. Both pH and temperature, independently, had a significant effect on the oxidative modifications mostly detected in myofibrillar proteins such as myosin and troponin and also collagen. Heat induced pyroglutamic acid formation was exclusively observed in the myofibrillar proteins. Potential interdependencies between pH, temperature and exposure time were evaluated using a 3-way analysis of variance (ANOVA) on protein modification levels to better understand how industry relevant process parameters influence protein quality and function. Abstract : Food Science; Food Analysis; Food Chemistry; Proteins; Meat processing conditions; Protein modifications; Proteomics